PENDEKATAN RESIKO KEHAMILAN KARTU SKOR POEDJI ROCHJATI (KSPR) DENGAN POLA RUJUKAN DI RSD dr. SOEBANDI JEMBER - Ai Nur Jannah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2014)
Approach to risk evaluation is an attempt to determine any possible risks in pregnancy can lead to maternal mortality and morbidity and premature babies. Hadijono in getting the results of his research on maternal mortality high risk pregnancy is 20 times higher than the low-risk pregnancies, perinatal mortality also obtained six times higher. The death of one of the problems caused due to late referral. The purpose of this study to determine the relationship approach to risk pregnancy Rochjati Poedji Score Card (KSPR) with referral patterns. Analytic design of this study is the correlation with the population of pregnant women who were referred in RSD dr. Soebandi Jember during month of April to June of 2013, as many as 320 samples taken randomly. Measuring instrument is secondary data medical records. The results of risk pregnancies and referral patterns indicate a low risk of pregnancy complications 12%, 62% of high risk pregnancies and pregnancies are very high risk 27%, 96% planned referral patterns and 4% referral fee. Chi-Square statistical test with significance level of 5% and df = 2 price obtained χ ² = 7.93 is greater than the table χ ² (7.93> 5.591) and the contingency coefficient obtained KK = 0.16 which means that there is a low relationship Among approach KSPR risk pregnancies with referral patterns. There are other factors that affect referral patterns, but with intensive approach to risk and maternal health services through a family-based problem-based pregnancy and safe delivery of the package, it will prevent the occurrence of late referral.